Design of a small-scale wind tunnel for the study of horizontal-axis wind turbine blades - Pankratov, E V; Kangash, A I; Kosarev, I A; Maryandyshev, P A (IOP conference series. Earth and environmental science, 2023)
The paper considers the details of design and construction of a small-sized wind tunnel with an open circuit and a closed test section for investigating the blades of horizontal-axis wind turbines. The effect of different types of jet straighteners on the turbulence of the flow in the test section has been studied. Turbulence flow distributions Tu at Reynolds numbers Re from 5·10 3 to 2·10 4 are obtained using Laser Doppler Anemometry methods. As a result, the wind tunnel design with average flow turbulence of 1.6 % is obtained. The flow visualization of NACA 64-618 airfoil at Re = 5·10 3 is obtained.